MODULE DEVELOPMENT TO IMPROVE TEACHERS' UNDERSTANDING OF HISTORICAL THINKING AT MGMP HISTORY BALANGAN REGENCY - setyawan, dharma (JURNAL SOCIUS, 2025)
History learning in schools has not yet optimally implemented the historical thinking approach. Consequently, appropriate instructional modules are needed to support teachers in facilitating historical thinking–based learning. This study aims to develop a valid and effective historical thinking module and to examine its impact on teachers’ understanding of historical thinking concepts. The research employed a research and development (R&D) method based on a modified Borg and Gall development model. The development process included needs analysis, module design, expert validation, revision, and limited implementation. The results of the study indicate that the material expert validation yielded a score of 79.16%, categorized as “very valid,” while media expert validation achieved a score of 80%, also classified as “very valid.” The average expert validation score was 79.58%, confirming that the developed module meets high validity standards. Expert evaluations further revealed that the module is highly feasible for use by teachers, particularly in supporting their understanding of historical thinking concepts within the History Subject Teachers’ Forum (MGMP) of Balangan Regency. The effectiveness of the module was demonstrated through an increase in teachers’ understanding of historical thinking concepts after using the module. The average level of teachers’ understanding increased from 47 before implementation to 87 after implementation, reflecting an improvement of approximately 85.00%. This level of improvement falls into the “very good” category. In conclusion, the historical thinking module developed in this study is both valid and effective and can significantly enhance teachers’ understanding of historical thinking, thereby supporting the improvement of history teaching practices in schools.